Sistem Penunjang Keputusan Menggunakan Algoritma Topsis Untuk Penerimaan Karyawan - Ady Widjaja; Icha Mailinda (Ikatan Ahli Informatika Indonesia, 2019)
A good and quality workforce is obtained by selecting or selecting prospective workers. The process of selecting employees at PT. Qdc Technologies, still using conventional methods, this results in the processing of prospective employee data requiring a long time, frequent errors so that many prospective employees or applicants who do not fit the criteria or company needs can be accepted to work in the company. This research will build a recruitment selection system using the Technique for Order Performance Similarity to Ideal Solution (TOPSIS) method, the TOPSIS algorithm was chosen because it has several advantages, namely, the first concept is simple and easy to understand, the next is the efficient and efficient computation process. from the implementation and testing that has been done it is proven that by using a system that has been designed, it is proven that the data processing process of prospective employees becomes faster, and by using the TOPSIS algorithm it is proven to be able to minimize errors, so that only prospective employees or applicants who are in line with company needs can hired. After evaluating and calculating using the TOPSIS algorithm, the results obtained are Alternative Ridha Firyadi with the final value of 0.561 and the lowest value obtained by Laela Febriani with a value of 0.336. So that the alternative chosen to be an employee is Ridha Firyadi with a value of 0.561.